Does information help to overcome public resistance to carbon prices? Evidence from an information provision experiment - Fabienne Cantner; Geske Rolvering (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2022)
To study how different economic information affect people's perceptions and attitudes towards carbon prices, we conduct an online survey experiment in a representative sample of the German voting population. We find that providing information about the efficiency of carbon prices as well as on international emission levels and carbon price initiatives changes people's perceptions and their support. Information about the possibility and benefits of revenue recycling, however, only affect the views of very specific subgroups of the population, such as individuals with low income or high trust in the government. Moreover, we find that none of the information affects the perceptions and support of climate change skeptics.
Keywords: D72; D83; D91; H23; Q58; 330; climate change; climate policies; carbon pricing; information; surveyexperiment